Combined 23-gauge sutureless vitrectomy and clear corneal phacoemulsification for rhegmatogenous retinal detachment repair - Moon, Hoseok; Sohn, Hee Jin; Lee, Dea Yeong; Lee, Jong Yeon; Nam, Dong Heun (International journal of ophthalmology, 2015)
AIM: To assess the outcomes of combined 23-gauge sutureless vitrectomy and clear corneal phacoemulsification with intraocular lens implantation for rhegmatogenous retinal detachment(RRD) repair.METHODS: This was a retrospective, consecutive,noncomparative, interventional case series of 30 eyes of30 patients who underwent combined sutureless vitrectomy and clear corneal cataract surgery for the repair of RRD. The principal outcome measures were primary anatomical success rate, reasons for redetachment, final visual acuity, and surgical complications.RESULTS: Primary reattachment was achieved in 27eyes(90.0%). The reasons for redetachment(3 eyes, 10%)were incomplete laser retinopexy, persistent chronic subretinal fluid, and proliferative vitreoretinopathy,respectively. The logarithm of the minimum angle of resolution visual acuity(mean±SD) improved from 0.76±0.74 preoperatively to 0. 21 ± 0. 37 6 months’ postoperatively(P <0.0001). Postoperative hypotony was not detected,but 1 eye( 3. 3 %) had increased intraocular pressure(30 mm Hg) with spontaneous resolution. No endophthalmitis developed during follow-up. Macular pucker was detected in 3 eyes(10.0%).· CONCLUSION: Combined 23-gauge sutureless vitrectomy and clear corneal phacoemulsification with intraocular lens implantation for RRD repair was proven safe and effective. It may provide not only the known advantages of conventional combined surgery, but also additional advantages such as less conjunctival fibrosis and the maintenance of stable intraocular pressure with low risks of postoperative hypotony and intraocular pressure elevation.